Factors Affecting The Readiness Of Sharia Paylater Implementation At Universitas Negeri Jakarta - Awaluddin, Rifaat Imappaganti; Indiyah, Fariani Hermin; Hendarno, Ari (IJBLE Scientific Publications Community Inc., 2024)
One of the results of technological developments that are being discussed in various parts of the world lately is Financial Technology (Fintech). As an innovation in the financial sector in non-bank financial institutions that utilize information technology as a tool to reach consumers. Make it easier for humans in the transaction process between buyers and sellers and can anticipate fraud in the transaction process. This study aims to examine the factors that affect the readiness of the implementation of sharia Paylater within the scope of Jakarta State University. These factors are; (1) optimism (2) innovasian; (3) discomfort; (4) insecurity; (5) perceived usefulness; (6) perceived ease of use; and (7) organizational culture. The method used in this study is a quantitative approach, using scale instrument tools. This method is used to determine consumer readiness to use the Paylater payment system using the Technology Readiness Acceptance Model (TRAM). The population of this study was all employees of Jakarta State University as many as 1714 respondents, consisting of civil servants and non-civil servants. After sampling was carried out, 95 respondents were obtained. Data analysis techniques using smartPLS software, are carried out to make measurements, both measurement models and structural models. The results of structural model analysis, as an analysis to determine the relationship between constructs hypothesized by researchers based on established criteria, show that of the 11 hypotheses proposed, there are 4 (four) hypotheses that are not significant. The four insignificant hypothetical relationships are; (1) INS - PU; (2) INS - PEU; (3) PEU - IU; and OC - IU. The four relationship models are issued in the model to describe the factors that affect the readiness of sharia paylater implementation at Jakarta State University.